Multispectral Polarization‐Insensitive Graphene/Silicon Guided Mode Resonance Active Metasurfaces - Prateeksha Sharma; Dor Oz; Eleftheria Lampadariou; Spyros Doukas; Elefterios Lidorikis; Ilya Goykhman (Advanced Photonics Research, 2025)
An advanced complementary metal‐oxide‐semiconductor (CMOS)compatible graphene/silicon multispectral active metasurfaces are investigated based on guided‐mode resonance filters. The simulated results show a high extinction ratio (>25 dB), narrow linewidth (≈1.5 @1550 nm), quality factor of Q ≈ 1000, and polarization‐insensitive operation. By taking advantage of graphene broadband absorption, the device operation is presented in the multiple spectral bands (NIR‐MIR) using simple geometrical scaling rules. The same device architecture can be employed for combined electro‐optic and thermo‐optic tuning using graphene as an integrated microheater. This work contributes to the development of advanced broadband silicon‐based active metasurfaces for tunable spectral filters and laser mirrors, optical switches, modulators, and sensors.